Analisis Marketing Mix dalam Meningkatkan Penjualan Produk UMKM Tempe di Kecamatan Marbau - Shinta Wulan Sinar Hati; Zulkarnaen Nasution; Syukron Arjuna (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the effect of marketing mix, consisting of product innovation, distribution channels, and product quality, on increasing sales of tempeh UMKM products in Marbau District. Tempeh UMKM in the area face challenges in increasing their competitiveness and sales volume. Therefore, this study uses a quantitative approach with a survey method to collect data from local tempeh UMKM actors. The variables analyzed include product innovation (additional variations and differentiation of tempeh), distribution channels (distribution media used to reach consumers), and product quality (product standards that affect customer satisfaction). the results of the study it can be concluded that product innovation has a positive and significant effect on increasing Sales, product quality has no effect and is not significant on increasing sales, distribution channels have a positive and significant effect on increasing sales and Product innovation, product quality and distribution channels have a positive and significant effect on increasing Sales.